Selection of vacuum pump system for steel degassing. Issue 2 (3rd June 2014) - Burgmann, W.; Gustafson, T.; Davené, J.
<x content-type="archive" xml:space="preserve">Abstract</x> Steam ejector vacuum pumps (SVPs) are mainly used on larger melt sizes up to 350 t in integrated steel plants because of the availability of steam. The use of dry operating mechanical vacuum pumps (MVPs) for steel degassing has made a tremendous step forward in the past 10 years but is still confined to melts below 150 t while its progress towards larger melt sizes is not completed. Besides the consideration of investment and operating costs there is no restriction in using any type of modern vacuum pump system for all vacuum processes and plant designs. Both systems fulfil all metallurgical requirements. Considering the significant savings in operating cost offered by MVP systems it is worth reconsidering the efforts for reducing air leaks, the use of protective gases and pressure losses between the pump set and the metallurgical reaction vessel. Both systems have made progress in energy optimising but the MVPs have a striking energy advantage. Only the overall costs should be considered, including those necessary to meet emission constraints and safety standards, and only the pressure prevailing at the reaction vessel is to be considered when comparing vacuum pump systems. Also, the means and use of dust abatement systems should be reconsidered since they offer cost savings by reducing the frequency of cleaning, less wear, little sludge handling and the significantly lower design suction capacity of SVP systems. The SVP mass flow need is to be corrected by a special coefficient before being applied to the volume conveying MVPs. Depending on the operational pressure required for the pump design, MVP systems can reach the same performance at the reaction vessel with much less mass flow capacity than that needed by a SVP system.